How children in Sweden accessed and perceived information during the first phase of the Covid-19 pandemic. Issue 1 (February 2022) - Rydström, Lise-Lott; Ångström-Brännström, Charlotte; Blake, Lucy; Brayl, Lucy; Carter, Bernie; Forsner, Maria; Matsson, Janet; Nilsson, Stefan; Jenholt Nolbris, Margaretha; Kirton, Jennifer; Kull, Inger; Protheroe, Joanne; et al.
Aim: To describe how children in Sweden accessed and perceived information about SARS-CoV2 and Covid-19 during the first phase of the outbreak. Methods: This study is a substudy of an international cross-sectional online mixed methods survey examining elements of children's health literacy in relation to Covid-19. The survey included multiple-choice questions, open-ended questions and drawings and collected information from 50 Swedish children (7–12 years). Data were analysed concurrently on a descriptive level using statistics and content analysis. Quantitative and qualitative data, including the drawings, were considered equally important and resulted in six categories, illuminating how children accessed and perceived information about the pandemic. Results: The survey showed that children accessed information mainly from school but also from TV. They preferred information from reliable sources. Children reported the information they accessed as easy to understand and it prompted them to ask new questions. They reported they knew a lot about the pandemic, for example, the potential danger to themselves and others and how to act to protect themselves and others. They perceived the pandemic as an intrusion on their lives. Conclusions: This study indicates that Swedish children between 7 and 12 years old were well informed about SARS-CoV2 and Covid-19 during the first phase of the pandemic. School was shown to be an important source of information. The children could explain how to act to protect themselves and others from becoming infected by the virus.